Penanganan Stunting Di Kabupaten Sumedang, Kabupaten Subang Dan Kabupaten Garut - Cecep - Hasanudin; Akadun - Akadun; Dadi Mulyadi Nugraha (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2022)
The problem of stunting is a very difficult problem to handle, especially in developing countries like Indonesia. According to the Basic Health Research data of the Indonesian Ministry of Health (Riskesdas) in 2018, the prevalence rate of stunting in Indonesia is 8.7 million or 30.7% of infants under five years of age (toddlers), in this case the figure is still above the target set by the Health Agency. World (WHO) by 20%. The problem of stunting is no exception in West Java Province, especially in three districts (Sumedang, Subang, Garut). The method in this research is the method used in writing this article is literature study. Literature study is an activity to gather information relevant to the topic or problem being the object of research. From the results of this study, it can be concluded that the stunting rate is still high due to many factors including poverty, the level of education / knowledge about health, and poor parental lifestyle, such as smoking, drugs, and others. There are various strategies for dealing with stunting in the three districts, but they are basically almost the same, namely the beginning, namely improving coordination of all parties and providing understanding of the importance of preventing stunting early on.